2020
DOI: 10.1371/journal.pone.0228804
|View full text |Cite
|
Sign up to set email alerts
|

Can syndromic surveillance help forecast winter hospital bed pressures in England?

Abstract: BackgroundHealth care planners need to predict demand for hospital beds to avoid deterioration in health care. Seasonal demand can be affected by respiratory illnesses which in England are monitored using syndromic surveillance systems. Therefore, we investigated the relationship between syndromic data and daily emergency hospital admissions. MethodsWe compared the timing of peaks in syndromic respiratory indicators and emergency hospital admissions, between 2013 and 2018. Furthermore, we created forecasts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Therefore, syndromic surveillance (such as ILI rates, which in Italy are provided weekly by the National Health Service Sentinel System) may be able to provide early warning of hospital bed capacity strain caused by seasonal respiratory disease. 26 To our knowledge, there is no study linking all this information together to ED visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, syndromic surveillance (such as ILI rates, which in Italy are provided weekly by the National Health Service Sentinel System) may be able to provide early warning of hospital bed capacity strain caused by seasonal respiratory disease. 26 To our knowledge, there is no study linking all this information together to ED visits.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, they found that predicting ED visits by considering both seasonality and ILI rates, compared with a model taking into account only seasonality, notably increased the fitting of the model. Therefore, syndromic surveillance (such as ILI rates, which in Italy are provided weekly by the National Health Service Sentinel System) may be able to provide early warning of hospital bed capacity strain caused by seasonal respiratory disease 26. To our knowledge, there is no study linking all this information together to ED visits.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal periodicity of hospital admissions has been described, 9,12 especially for influenza. 13,14 Seasonal periodicity has also been described for cerebrovascular, 15 cardiovascular, 16,17 and gastrointestinal 18 pathologies and may relate to weather patterns, the availability of services, and patient behaviours. 19 Weekly and daily periodicity might also relate to pathogenesis of the diseasefor example demand distribution of cardiovascular disease peaks in the late morning and there are greater case numbers on Mondays [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, data on general practice (GP) physician in-hours and out-of-hours consultations are collected, among others. These existing syndromic data sources [ 15 ] were previously used in studies focused on defining early warning indicators and algorithms for gastrointestinal illness [ 16 ] and norovirus [ 17 ] and also real-time predictions informing forecasts of hospital admissions due to respiratory illness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%